2021
DOI: 10.1108/ribs-12-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

Can blockchain-technology fight corruption in MNEs’ operations in emerging markets?

Abstract: Purpose The purpose of the study is to explore, with anchorage in theories about the normalization of corruption, under what conditions blockchain technology can mitigate corruptive practices of multinational enterprises (MNEs) in emerging markets (EMs). Design/methodology/approach By synthesizing a technological perspective and theory on corruption, the authors examine the feasibility of blockchain for fighting corruption in MNEs’ business operations in EMs. Findings Blockchain technology is theorized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…Such an introduction might use a shared immutable electronic ledger such as blockchain with added benefits of transparency through a disruption of the social construct of corruption. It may be used to counteract opportunistic economic activities, that is, corruption or financial waste, by providing economic incentives to maintain the blockchain consensus (Davis et al , 2021). Finally, morality and ethical behaviour should play a central role in overcoming market imperfections, and this is true not only for the parties involved in construction development but also for the industry as a whole.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Such an introduction might use a shared immutable electronic ledger such as blockchain with added benefits of transparency through a disruption of the social construct of corruption. It may be used to counteract opportunistic economic activities, that is, corruption or financial waste, by providing economic incentives to maintain the blockchain consensus (Davis et al , 2021). Finally, morality and ethical behaviour should play a central role in overcoming market imperfections, and this is true not only for the parties involved in construction development but also for the industry as a whole.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…To curb irregularities, Davis et al (2022) examined the conditions in developing economies that blockchain technology (BT) can alleviate corruption of multinational companies. The study found that BT is hypothesized to have different curbing influences on the socialization, justification and institutionalization of fraud.…”
Section: Electronic Procurement and Creative Accountingmentioning
confidence: 99%
“…Nasdaq, 2012). Emerging markets have been linked to specific challenges of doing business, which have been conceptually captured by international distances (Davis et al, 2021). According to Ghemawat's (2001) CAGE framework, international distances to, e.g.…”
Section: Introductionmentioning
confidence: 99%